Pengaruh Model Pembelajaran Kooperatif Learning Tipe Teams Games Tournament (TGT) Terhadap Motivasi Belajar Siswa pada Materi Green Chemistry: Penelitian - Mayora Febsi Khairatul; Rayandra Asyhar; Epinur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effect of the TGT model on students’ learning motivation in Green Chemistry. The research method used is a quasi-experimental design with a Non-Equivalent Control Group. The sample was selected using purposive sampling, consisting of two classes: the experimental class, which applied the TGT model, and the control class, which used the Think Pair Share (TPS) model. Research instruments included observation sheets and a learning motivation questionnaire. The data were analyzed using normality and homogeneity tests, independent and paired t-tests, and ANCOVA to determine the effect of the learning model on students’ motivation.The results showed that the data were normally distributed and homogeneous. The average final questionnaire score for the experimental class was 117, while the control class scored an average of 102. The independent t-test yielded a sig. (2-tailed) value of 0.000, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted, meaning there was a significant difference between the experimental and control classes. The paired t-test showed that both classes experienced a significant increase in learning motivation, but the increase was greater in the experimental class. Furthermore, the ANCOVA results demonstrated that after controlling for covariate variables, the TGT model still had a significant effect on students’ learning motivation.In conclusion, the TGT model positively influences students’ learning motivation at SMA N 11 Muaro Jambi on the topic of Green Chemistry. This model can serve as an alternative instructional strategy that is more engaging and effective for teaching chemistry.